The university role in developing the human capital for a sustainable bioeconomy - Ruxandra Bejinaru; Cristian Valentin Hapenciuc; Iulian Condratov; Pavel Stanciu (Amfiteatru Economic Journal, 2018)
The developments in the bioeconomy area should reflect their usefulness regarding the provision of sustainable solutions for future competitiveness growth by using mainly natural resources. Nowadays the relevance of education, training and research in bioeconomy domain is obvious because these types of solutions which may be generated mainly by educated individuals who contribute to the better specialization of the human capital on this market. The aim of the research is to analyze the influence of universities upon the human capital activating in the bioeconomy sectors throughout the transfer of three types of knowledge: rational, emotional and spiritual. This goal is transposed into practice throughout exploratory quantitative research among students. The data obtained were then processed by factorial analysis in SPSS v.20, resulting in three relevant dimensions describing the phenomenon investigated. These factors manage to capture the facets of human capital in interdependence and interrelation with the dimensions of bioeconomy. The originality of the paper consists in formulating the research assumptions based on the nonlinear principles and components of the new entropic model of the intellectual capital of the organization. The study can be a starting point for designing strategies for increasing the human capital of organizations in various fields as well as of systems in the bioeconomy field.
Keywords: I25; J24; O34; Q57; 330; bioeconomy; human capital; intellectual capital; university; emotional knowledge; spiritual knowledge; rational knowledge; sustainable development